Boosting Africa’s Competitiveness - Ramos, M. (ORASIS Global Meeting - Cascais 27-30 May, 2017)
Despite Africa’s rapid growth over past years, inequality remains high and economic competitiveness is lagging behind other world regions. Which African nations might lead, which may follow, and which may need help? What might hinder change?